Effectiveness of hybrid project-based learning with digital portfolios in enhancing mathematics pedagogical content knowledge - Agustika, Gusti Ngurah Sastra; Diputra, Komang Sujendra (Indonesian Journal of Educational Development (IJED), 2025)
This study investigates the effect of the Hybrid Project-Based Learning (PjBL) model integrated with digital portfolios on the enhancement of Mathematics Pedagogical Content Knowledge (MPCK) among primary teacher education students. The urgency of this research stems from the persistent gap in teacher education, where traditional methods inadequately develop MPCK in prospective teachers. The main objective was to examine whether the hybrid PjBL model, which combines project-based learning and digital tools, can significantly improve MPCK in primary teacher education students. The research uses a quasi-experimental design with a posttest-only control group. The population consists of primary teacher education students, with a purposive sampling technique used to select two regular classes, each comprising 32 students. The experimental group was exposed to hybrid PjBL, while the control group followed conventional teaching methods. Data were collected using the MPCK scale, a 40-item instrument designed to assess students' mathematical pedagogical competencies. Data analysis was conducted using an independent sample t-test after ensuring normality and homogeneity of variance. The results indicated that the experimental group achieved significantly higher MPCK scores, demonstrating the effectiveness of the hybrid PjBL model in enhancing MPCK. Based on these findings, it is recommended that teacher education programs integrate hybrid PjBL models with digital portfolios to improve MPCK development among prospective teachers.